How to sequence video modeling examples and inquiry tasks to foster scientific reasoning. (December 2017) - Kant, Juliane M.; Scheiter, Katharina; Oschatz, Kerstin
Abstract: Scientific reasoning skills can be acquired through technology-enhanced inquiry tasks or video modeling examples showing how to conduct virtual experiments. However, inquiry tasks can be cognitively demanding for novice learners, whereas video modeling examples can induce overconfidence. The present study investigated the effectiveness of both approaches in isolation and combination. We compared the effects of four groups (example-example, example-task, task-example and task-task) on learning outcomes, perceived difficulty and mental effort, judgments of learning, and monitoring accuracy among 107 seventh graders. In line with our hypotheses, watching a video modeling example first led to lower mental effort, better learning outcomes, and higher judgments of learning than solving an inquiry task first. Contrary to our hypotheses, all groups underestimated their performance. Results for mental effort and learning outcomes corroborate research on worked examples, whereas results for judgments of learning and monitoring accuracy indicate an underconfidence-with-practice effect. Highlights: Sequence of examples and tasks affected acquisition of scientific reasoning skills. Example-first groups experienced lower cognitive load than task-first groups. Example-first groups had better learning outcomes than task-first groups. Example-first groups had higher judgments of learning than task-first groups. All groups underestimated their scientific reasoning performance.